Sogdian Acculturation in Medieval China (fifth through ninth centuries): A Study of Sogdian Tombs Found in China - LYU, PIN (2024)
The Middle Ages (defined here as the period from the fifth to ninth centuries) were surprisingly among of the most vibrant eras in Chinese history. This was due to the intense cross-cultural interactions occurring in northern China and its direct involvement in the flourishing land-based silk roads across Eurasia. From the Northern Wei (386-534 CE) to the Northern Zhou (557-581 CE) and the Northern Qi (550-577 CE), nomadic Xianbei rulers created and consolidated a ruling coalition composed of multiple cultural and ethnic groups in northern China. When Han Chinese unified all of China in the Sui (581-618 CE) and the Tang (618-907 CE) Dynasties, China retained much of its cosmopolitan feel. During the centuries-long vibrant era, many non-Han people moved to China and experienced frequent cultural exchanges in Chinese society, among which Sogdians were a remarkable ethnic group. The recently excavated Sogdian tombs in northern China provide new insight into long-discussed questions concerning Sogdian cultural adaptation in medieval China (fifth to ninth centuries). This thesis collects almost all extant materials related to these Sino-Sogdian tombs, and based on these materials, provides a comprehensive study of the patterns of the Sogdian lifestyles reflected in their tombs and mortuary objects. Eschewing the overused theory of Sinicisation, this thesis proposes an analytical framework based on the theory of acculturation to examine the empirical evidence (i.e., Sino-Sogdian tomb complexes). The results indicate that Sogdians adopted Chinese funerary customs while maintaining their cultural heritage, which can be described as integration according to the theory of acculturation. The Sogdian integration was creative, as evident in some new funerary practices that neither originally existed in Chinese nor Sogdian backgrounds but were a new way of mixing two different cultural traits. This was also a dichotomic integration, likely under the pressure of Chinese government-dominated mild cultural assimilation. The Chinese burial traditions of the Sogdians were outwardly visualised, while their own ethnic or religious burial arrangements were hidden inside their tomb structures.